Pengaruh Getah Damar Sebagai Tambahan Campuran Asphalt Concrete-Binder Couerse (AC-BC) Terhadap Karakteristik Marshal - Arung Samudra Bahari; David Daniel Marthin Huwae; Penina T Istiah (Universitas Pahlawan Tuanku Tambusai, 2024)
Arung Samudra Bahari, Nim 1319174057 “the effect of resin as an addition to Asphalt concrete - binder course (AC-BC) mixture on marshall characteristics”. Thesis, Road and Bridge Construction Engineering Study Program, Department of Civil Engineering, Polteknik Negri Ambon. This thesis is under the guidance of David Daniel Marthin Huwae. S T., MT. and Penina T. Istiah, S Pd., M. Si. In the resin tree there is sap which contains essential oils and there is also resinol acid which has sticky, hard, and also melts easily. The resin will harden and then melt again depending on certain temperature changes. The effect of adding rosin sap to the asphalt mixture proves that the characteristics of asphalt are not much different from proving asphalt in general, but the results obtained on asphalt combined with rosin sap have increased elastic power which still maintains the unity of its shape due to high pressure. The use of resin can make asphalt mixtures more able to withstand road damage due to changes in weather and climate, the purpose of this study is to analyze the characteristics of Asphalt Concrete - Binder Course (AC-BC) levels in the presence of added resin and analyze the comparison between the addition and without the addition of resin to the Asphalt Concrete-Binder Course (AC-BC) mixture on marshall characteristics using 2% and 3% resin levels. As carried out in the Laboratory of the Maluku Ambon Road Implementation Center with reference to the requirements published by the Directorate General of Highways at KAO. The data collection method used in this study is the collection of primary data obtained based on several test objects from various treatment conditions tested in the laboratory such as marshall test results which include density, VIM (void this mix), VMA (void this mineral aggregate), VFA (void filled with asphalt), stability, flow (melting), and MQ (marshall quotient). And secondary data obtained from literature studies. The overall test results that meet the requirements in the 3% resin mixture with 5%, 5.5%, 6% asphalt content meet the specification requirements that have been listed with the 2018 bina marga specifications. So it can be concluded that the greater the presentation of resin content, the higher the quality value.